New voltammetric and spectroscopic studies to quinacrine-DNA-Cdots interaction. (20th May 2019) - Oliveira, R.; Amaro, F.; Azevedo, M.; Vale, N.; Gonçalves, H.; Antunes, C.; Rego, R.
Abstract: The interaction of antimalarial drug quinacrine (QC) with salmon sperm double stranded DNA was studied on three sets of glassy carbon electrodes (GCEs) modified with DNA, carbon dots (Cdots) and DNA + Cdots mixture at pH values of 4.5 and 7.4. For the first time, Cdots were used in studies of drug-DNA interactions. DNA binding was investigated by cyclic and differential pulse voltammetry (CV and DPV), fluorescence quenching, UV–vis absorption and FTIR spectroscopy, suggesting that QC acts as efficient DNA binder. DPV response of the QC on modified electrodes is pH-dependent. On modified GC electrodes the oxidation peak current/charge change and the oxidation peaks shifted to positive values. Stern-Volmer (KSV ) and binding constants (Kf ) determined from fluorescence measurements were KSV of 8.8 × 10 3 M −1 and Kf of 2.0 × 10 4 M −1 and KSV of 8.3 × 10 3 M −1 and Kf of 3.2 × 10 4 M −1, for pH 4.5 and 7.4, respectively. Static single binding intercalation seems to be the main interaction process between QC and DNA at both pH values. Moreover, UV–vis and FTIR studies confirmed the interaction between QC and DNA. The overall results suggested that QC binds to DNA essentially through intercalation mode.